Predicting the potential distribution of the invasive weed Mikania micrantha and its biological control agent Puccinia spegazzinii under climate change scenarios in China - Wei Zhang; Qing Huang; Yingzhi Kuang; David Roy Clements; Gaofeng Xu; Fudou Zhang; Shicai Shen; Lun Yin; Michael Denny Day (Biological Control)
Research on the potential distribution of invasive plants and their biological control agents under climate change is critical for informing strategies in invasive species management. The rust fungus Puccinia spegazzinii shows significant potential as a biological control agent for the invasive weed Mikania micrantha. The MaxEnt (Maximum Entropy) model was used to simulate the distribution of M. micrantha and P. spegazzinii under current and future climate scenarios. The models achieved excellent prediction performance, with M. micrantha and P. spegazzinii having area under the curve values of 0.921 and 0.978 respectively, and true skill statistics values of 0.886 and 0.902 respectively. Precipitation is the primary factor influencing the distributions of M. micrantha, while P. spegazzinii is determined by both temperature and precipitation. The suitable areas for the two species are concentrated in southern China, with M. micrantha exhibiting broader adaptability compared to P. spegazzinii. Under future climate scenarios, the suitable areas for M. micrantha in China will expand northward, with a maximum projected growth rate of 84.6 % in the 2070 s, whereas P. spegazzinii exhibits a contracting trend (with a projected reduction of 40.8 % in the 2050 s). Under the current climate scenario, the overlapping suitable areas between the two species account for 25.2 % of the total suitable area for M. micrantha and 100 % of that for P. spegazzinii and both remain relatively stable under future climate scenarios. This work can provide guidance for the application of biological control, and serves as a valuable reference for developing early warning and management response strategies for invasive species in China.